Politics, ideology and the development of modern geography in China - Hausherr, Inka Bianca (ERDKUNDE, 2003)
This contribution discusses the development of modern Chinese geography within its historical context. Special emphasis is put on the influence of ideological and political currents on the development of (geographical) science. In this light, three distinct, yet interconnected phases of modern Chinese geography are distinguished: 1. Modern phase of geography, which was initially influenced by the West, then started to develop an institutional structure of its own and spread from the coastal cities to the Chinese hinterland, always under the influence of the changing political tides at work; 2. A phase of reorganisation and isolation after the founding of the People’s Republic of China (PRC), first under intensive Soviet influence, then culminating in a near total standstill during the Cultural Revolution; 3. Finally, the Contemporary phase of geography, which is once again characterized by an increasing openness to the international scientific community, similar to the first phase. Indicators of change are found on the institutional level and on the contents level of geographical science. In the light of these rapid changes within one century, a reflection of the objectivity of geographical science is attempted which includes the extended context of science, i.e. its embedding in the political and ideological environment.